The Origin of Asian Financial Crisis and Methods of its Overcoming - Ostalecka, Agnieszka (Przyczyny azjatyckiego kryzysu finansowego i metody jego przezwyciężania, 2010)
The main objective of this article is to identify the reasons of East Asia financial crisis outbreak and to present the methods of crisis overcoming. The interventional activities, which were used to meet this goal, were proceeded in two directions: increasing liquidity in banking system and restoring confidence to the banking sector. The most important actions taken in order to restore liquidity in the banking system were liquidity support from the central bank and decreasing the level of banks financial reserves. Whereas the remedies directed on restoring confidence were as follows: enforcing deposit insurance system, financial support from international financial institutions (IMF, World Bank) and conducting the reforms of the banking system including the program of banks restructuring.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 78-90
Keywords: financial crisis; crisis spreading; crisis overcoming